The Influential Factors of Corporate Culture on Knowledge Sharing Among Employees in Small and Medium-Sized Enterprises in the Private Sector in Hanoi - Anh, Nguyen Tuan; Duong, Nguyen Duc (Journal of Posthumanism, 2025)
Today, knowledge has become a vital resource for enhancing the competitiveness of enterprises. In Vietnam, although knowledge management is not yet widely adopted, both large and small businesses have begun to pay attention to promoting knowledge sharing. To improve the competitive advantage of Vietnamese enterprises—especially small and medium-sized enterprises (SMEs) in the private sector, a dynamic segment of the economy—encouraging knowledge sharing among employees is considered one of the most effective solutions. However, previous studies have shown that knowledge sharing is heavily influenced by corporate culture factors. Based on Mueller’s (2013) model, this study examines the impact of corporate culture elements on knowledge sharing. The survey sample includes 479 employees working at SMEs in the private sector in Hanoi. These private enterprises in Hanoi have continuously developed and innovated, contributing more than 40% of the city’s GDP and creating jobs for over 50% of the workforce. This demonstrates that SMEs in Hanoi’s private sector are playing a key, pioneering role in the capital and national development.